Sport Massage and Lactic Acid Recovery Time in Softball Athletes - Tono Haryono; Jajat Darajat; Agus Rusdiana; S Salman; Agus Gumilar (Universitas Pendidikan Indonesia, 2021)
Various factors causing fatigue in athletes include an increase of lactic acid in muscles. According to the movement patterns of softball athletes, the energy source comes from the Lactaid anaerobic metabolism. Therefore, it is necessary to know the elimination of lactic acid in muscles, reflecting the decrease of lactic acid in the blood. This study aimed to determine the recovery time of lactic acid levels after exercise in 0 minutes, 5 minutes, 10 minutes, and 20 minutes. Accutrend Lactacid measured softball athlete lactic acid levels. The method used in this study was an experimental method with One-Shot Case Study research design, while the research subjects were randomly assigned from the viable softball athlete population in the Student Activity Unit. The samples included 12 athletes. Data analysis employed t-test paired scores with significance p ≤ 0.05 using SPSS V. 20.0 software. The results showed that the lactic acid levels returned to normal, namely the level of 2.79 mMol/L, at 20 minutes of rest. It concludes that that lactic acid levels of softball athletes increased after the start of training, decreased after 5 minutes of rest, and returned to normal in 20 minutes of rest.